Protective Effect of Carotenoid Extract from Orange-Fleshed Sweet Potato on Gastric Ulcer in Mice by Inhibition of NO, IL-6 and PGE2 Production - Ji-Yeong Bae; Woo-Sung Park; Hye-Jin Kim; Ho-Soo Kim; Kwon-Kyoo Kang; Sang-Soo Kwak; Mi-Jeong Ahn (MDPI AG, 2021)
Ipomoea batatas (L.) Lam., Convolvulaceae is widely distributed in Asian areas from tropical to warm-temperature regions. Their tubers are known for their antioxidant, anti-bacterial, anti-diabetic, wound healing, anti-inflammatory, and anti-ulcer activities. The preventive and therapeutic effects of orange-fleshed sweet potato on gastric ulcers have not been investigated. In this study, the carotenoid extract (CE) of orange-fleshed sweet potato was found to protect against gastric ulcers induced by HCl/ethanol in mice. The anti-inflammatory and antioxidant activities of the carotenoid pigment extract were also evaluated as possible evidence of their protective effects. Administration of CE reduced gastric ulcers. Oral administration of CE (100 mg/kg) protected against gastric ulcers by 78.1%, similar to the positive control, sucralfate (77.5%). CE showed potent reducing power and decreased nitric oxide production in a mouse macrophage cell line, RAW 264.7, in a concentration-dependent manner. The production of the inflammatory cytokine interleukin-6 and prostaglandin E2 was also reduced by CE in a dose-dependent manner. The high carotenoid content of orange-fleshed sweet potato could play a role in its protective effect against gastric ulcers. This result suggests the possibility of developing functional products using this nutrient-fortified material.